Evaluasi Keberhasilan Transfer Embrio Sapi Limosin dan Performan Pedetnya di Kabupaten Tuban - Boluka, S B; Suroto, K S; Astuti, F K; Murti, A T (Politeknik Negeri Lampung, 2026)
This study evaluates the success of Limosin cattle embryo transfer (ET) and subsequent calf performance in Tuban Regency, Indonesia. The research employed a descriptive quantitative approach to detail observed events and relate them to research variables. Data was analyzed using descriptive and inferential statistics, including Service per Conception (S/C) and Conception Rate (CR). The study found a 25% ET success rate, which is at the lower end of the national standard (25-35%). This was influenced by the limited availability of productive recipients (only 26.67% of 75 cows were deemed suitable), suboptimal physiological conditions and Body Condition Scores (BCS) of recipients, and technical challenges such as imprecise estrus synchronization and technician skill. Additionally, the tropical dry climate in Tuban contributed to heat stress, potentially impacting embryo implantation. Despite these challenges, the resulting calves showed good performance, with average birth weights of 27-28 kg and daily weight gains (ADG) of 777.8-898.9 g/day, categorizing them as optimal for superior genetic beef cattle. This indicates that in vitro fertilization (FIV) embryos from superior donors can successfully transfer desirable genetic traits even when raised by local recipient cows. The study concludes that while challenges exist, ET holds significant potential for improving cattle genetic quality in Tuban